SEMANGAT SOLIDARITAS DI SAAT KRISIS: POTRET UNIVERSITAS DI BAWAH AFILIASI MUHAMMADIYAH DALAM PENANGANAN COVID-19 - syed agung afandi; Ardiansyah Ardiansyah; Al Fauzi Rahmat; M. Rafi (LPPM Universitas Abdurrab, 2023)
This article aims to explore the extent to which the universities under affiliation Muhammadiyah in handling Covid-19. The method in this paper using qualitative explorative with case study approaches. To capture the data and information related to the topic, we assisted by Qualitative Data Analysis (QDA) with NVivo 12 plus software. In this article, we focus on the philanthropic movements carried out by universities under the auspices of Muhammadiyah, taking examples from 6 Muhammadiyah Universities as a study to identify it. On the other hand, this study relies on essential variables from the philanthropic movement to conceptualize Giving, Services, and Association practices. We findings, universities under affiliation Muhammadiyah are taking part in dealing with Covid-19. Various actors are involved, not only from Muhammadiyah University but also from collaborating with other stakeholders such as Government, Community in response to the Covid-19 with various programs and activities initiatives. In Spirit of Giving, Muhammadiyah Universities have the most prominent intensity, with 54% divided on health, education, and social sectors. The Spirit of Service that universities have 20%, where many things initiate various programs and activities. Furthermore, the Spirit of Association with 18%, in which those Muhammadiyah Universities collaborate with other stakeholders such as internal and external actors. That is all in order to accelerate the elimination of the Covid-19 outbreak.